Initial nipple damages in breastfeeding women: analysis of photographic images and clinical associations - Bárbara Tideman Sartorio Camargo; Adriana Sañudo; Denise Miyuki Kusahara; Kelly Pereira Coca (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to analyze the initial nipple damage degree by breastfeeding practice and to associate findings with clinical manifestations of breastfeeding women. Methods: a retrospective, cross-sectional study with primary data and photographic images database from two randomized clinical trials. Photographic images were analyzed by two independent evaluators using the Nipple Trauma Score. For analysis, the chi-square, Mann-Whitney tests and Kappa coefficient were applied. Results: 115 breastfeeding women and their respective 186 photographic images were analyzed. The degree of agreement of evaluators using the Nipple Trauma Score was 93.6%. The nipple pain score during breastfeeding was moderate and compromised more than 25% of the nipple surface area. Conclusions: assistance to breastfeeding women should prioritize nipple pain intensity instead of the nipple damage size.